The Influence of #Benarberbahasa Hashtag on Instagram on the Use of Good and Correct Language among Zillenials - Wesa Nurrahim, Irsalinda; Nurliah, Nurliah; Juwita, Rina; Alfando WS, Johantan (PT ARRUS Intelektual Indonesia, 2024)
The aim of this research is to examine the influence of the #correctlanguage hashtag on Instagram related to the good and correct language use among zillenials in the city of Samarinda. This type of research utilized quantitative methods. The data collection technique used a questionnaire, a sample was collected of 100 respondents consisting of the millennial generation (aged 15 - 30 years) in the city of Samarinda. The research results reveal that the #Benarberbahasa hashtag has a significant positive influence on the good and correct use of Indonesian. In addition, it is found that media content and frequency of media use and media consumption also contributed to strengthening the impact of this hashtag. This study concludes that #Benarberbahasa hashtag is an effective digital campaign in influencing the use of good and correct Indonesian, as well as recommending similar strategies to be implemented by content creators or other linguistic activists in order to maintain the existence of Good and Correct Use of Indonesian